Yellow Brick Roadmap to Demand-Based Parking Pricing: Findings from Washington, D.C. Issue 12 (December 2019) - Dey, Soumya S.; Dock, Stephanie; Pochowski, Alek; Sanders, Meredyth; Pérez, Benito O.; Darst, Matt; Sanchez, Eduardo Cardenas
Washington, D.C. (the District) has been a national leader with its progressive approach to parking management. Owing to the District's strong housing and employment growth over the past decade, the District Department of Transportation (DDOT) needs a program to balance the competing parking needs of residents, commuters, visitors, and businesses. Using Federal funding from the Federal Highway Administration (FHWA) Value Pricing Pilot Program, DDOT planned and implemented a demand-based parking pricing pilot program in the Penn Quarter and Chinatown neighborhoods. The results of the pilot program confirmed that demand-based pricing programs can be both cost-efficient and effective, and highlighted a path to expanding demand-based pricing Districtwide. Using lessons learned from this project, practitioners will be better prepared to plan their own demand-based pricing programs, positioning themselves to effectively balance parking supply and demand in their own communities. The paper discusses the impacts of demand based pricing on a range of metrics such as parking search times, cruising, occupancy, and length of stay. It also assesses the impacts of the strategies on the larger transportation system and the study area.